Healing the Broken Heart; The Immunomodulatory Effects of Stem Cell Therapy - Wagner, Marcus J.; Khan, Mohsin; Mohsin, Sadia (Frontiers in Immunology, 2020)
Cardiovascular Disease (CVD) is a leading cause of mortality within the United States. Current treatments being administered to patients who have suffered a myocardial infarction (MI) has increased patient survival but do not facilitate the replacement of damaged myocardium. Recent studies demonstrate that stem cell-based therapies promote myocardial repair; however, the poor engraftment of the transferred stem cell populations within the infarcted myocardium is a major limitation regardless of the cell type. One explanation for poor cell retention is attributed to the harsh inflammatory response mounted following MI. The inflammatory response coupled to cardiac repair processes is divided into two distinct phases. The first phase is initiated during ischemic injury when necrosed myocardium releases Danger Associated Molecular Patterns (DAMPs) and chemokines/cytokines to induce the activation and recruitment of neutrophils and pro-inflammatory M1 macrophages (MΦs); in turn, facilitating necrotic tissue clearance. During the second phase, the shift from the M1 inflammatory functional phenotype to the M2 anti-inflammatory and pro-reparative functional phenotype, permits the resolution of inflammation and the establishment of tissue repair. T-regulatory cells (Tregs) are also influential in mediating the establishment of the pro-reparative phase by directly regulating M1 to M2 MΦ differentiation. Current studies suggest CD4+ T-lymphocyte populations become activated when presented with autoantigens released from the injured myocardium. The identity of the cardiac autoantigens or paracrine signaling molecules released from the ischemic tissue that directly mediate the phenotypic plasticity of T-lymphocyte populations in the post-MI heart are just beginning to be elucidated. Stem cells are enriched centers that contain a diverse paracrine secretome that can directly regulate responses within neighboring cell populations. Previous studies identify that stem cell mediated paracrine signaling can influence the phenotype and activity of immune cell populations in vitro, but how stem cells directly mediate the inflammatory microenvironment of the ischemic heart is poorly characterized and is the topic of extensive investigation. In this review, we summarize the complex literature that details the inflammatory microenvironment of the ischemic heart and provide novel insights regarding how paracrine mediated signaling produced by stem cell-based therapies can regulate immune cell subsets to facilitate pro-reparative myocardial wound healing.